Pengaruh Good Governance dalam Pengelolaan Dana Desa Terhadap Kepercayaan Masyarakat: Suatu Persepsi dari Masyarakat di Kecamatan Pantai Cermin - Della Yuni Arianti; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to determine the effect of good governance (perceived accountability, perceived transparency, and perceived responsiveness) in the management of village funds in Pantai Cermin District on public trust. This type of research is causative with a quantitative approach. The population in this study was the people of Pantai Cermin District with a sample of people who were or had completed their education at tertiary institutions. Primary data in this study were collected by distributing a 5-point Likert scale questionnaire. SPSS software version 24 is used as a tool in processing research data and multiple linear regression analysis is used as a data analysis technique in this study. The results of the study show that perceptions of accountability have no partial effect on public trust; conversely, perceptions of transparency and responsiveness influence public trust. Simultaneously the three components of good governance affect the community's trust in the village government in Pantai Cermin District.